Effect of Weather Parameters on Population Dynamics of Coccinellids in Sugarcane - Ramya R; Kumar , Anil; Kumar , Nagendra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Study of the population dynamics of coccinellids were carried out from 28th to 12th SMW during 2022-23. Two species Micraspis yasumatsui and Cheilomenes sexmaculata were found active throughout the whole study period. The population of Coccinellaseptempunctata, Propyleadissecta, Coccinella transversalis first appeared from 30thSMW and reach their peak population during 2ndSMW, whereas the population of Micraspis yasumatsuiand Cheilomenes sexmaculata started from 28th SMW and reach their peak during 52nd and 2ndSMW respectively. The coccinellids showed positive and highly significant correlation with relative humidity and negative and highly significance with maximum temperature.